Caracterização espacial da atividade apícola na microrregião de Campos do Jordão, São Paulo, Brasil - Bendini, Juliana N.; Orsi, Ricardo de Oliveira [UNESP]; Bendini, Hélio N.; Souza, D. C.; Salum, R. B. (SciELO Espana/Repisalud, 2014)
This study aimed to generate a database related to the spatial distribution of hives and productivity of regional producers, through the Geographic Information System (GIS) using the Global Positioning System. To build the database of geographical information (GIS) software for processing of geo-referenced information was used. The microregion (4 municipalities and 54 beekeepers) shows concentrations (pockets) of beekeepers and hives in certain locations. Further studies are needed on the characteristics of the local flora for bees to infer about possible saturation of floral resources, since no differences were observed between honey production in apiaries isolated or inserted into the pockets. The GIS proved to be an efficient tool for monitoring the location and origin of regional production, and for planning the distribution of hives and apiaries and so, contribute to a better use of flora and improvement of productivity of the apiaries.

Objetivou-se gerar uma base de dados relacionada à distribuição espacial, de colmeias e produtividade dos apicultores regionais, por meio do Sistema de Informações Geográficas (SIG) utilizando-se o Sistema de Posicionamento Global. Para a construção do banco de informações foi utilizado o software de processamento de informação georreferenciada. A microrregião (4 municípios e 54 apicultores) mostra concentrações (bolsões) de apicultores e de colmeias em determinadas localidades. São necessários mais estudos sobre a flora apícola local para se inferir sobre saturação de recursos para as abelhas, já que não foram observadas diferenças de produção entre os apiários isolados ou inseridos nos bolsões. O SIG mostrou-se eficiente para o monitoramento da localização e procedência da produção regional e no planejamento da distribuição dos apiários e colmeias, podendo dessa forma contribuir para o melhor aproveitamento da flora local e melhoria da produtividade dos apiários.
Spatial characterization of beekeeping in the micro region of Campos do Jordao, São Paulo, Brazil
Keywords: Geographic Information System|Honey; Sistema Informação Geográfica; Mel